Problems and Perspectives of Organic Farming in Slovene Istria - Podmenik Adam, Dane; Kerma, Simon (Journal for Geography, 2009)
In Slovene Istria, natural conditions for the development of organic farming are good, though we have only witnessed the rise of organic farming over the last few years. Due to the lack of data related to organic farming in Slovene Istria, field-work was conducted in spring 2008 with some additional research in 2009. Questionnaires and interviews with organic farmers include various aspects: characteristics of their farming activities, demographic and socio-economic features, and others. The prevailing branches of organic farms in Slovene Istria are olivegrowing and mixed production. We can also mention a very high educational level of farmers and positive age-structure of households on organic farms. Possible perspectives related to organic farming in the studied area have been discussed in the conclusion of the paper.